2019
DOI: 10.2147/cmar.s214604
|View full text |Cite
|
Sign up to set email alerts
|

<p>Gain and loss from transcatheter intra-arterial limb infusion of cisplatin for extremity osteosarcoma: a retrospective study of 99 cases in the past six years</p>

Abstract: Purpose We intend to analyze the gain and loss from transcatheter intra-arterial (IA) limb infusion of cisplatin for extremity osteosarcoma in the past six years. Patients and methods Between December 2009 and August 2014, a total of 99 patients were analyzed for efficiency and followed up for long-term survival. Based on the different administration methods of cisplatin, we divided them into the following two cohorts: IA infusion of cisplatin (n=48) and intravenous (IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Although systematic adverse events, including nausea, vomiting, anemia and an increase in creatinine/aminotransferase levels, shared similar incidence rates and severities with the study reported by Xie et al, local skin hyperpigmentation and pelvic soft tissue necrosis in muscle occurred after only 3 and 1 of 24 CAI events (12.5% and 4.2%, respectively), which is more favorable than the situation reported in the most reviewed studies concerning extremity osteosarcoma. (13,29,32) This nding could be explained by the shorter local drugretention time since the pelvis has a more su cient blood supply and drainage.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although systematic adverse events, including nausea, vomiting, anemia and an increase in creatinine/aminotransferase levels, shared similar incidence rates and severities with the study reported by Xie et al, local skin hyperpigmentation and pelvic soft tissue necrosis in muscle occurred after only 3 and 1 of 24 CAI events (12.5% and 4.2%, respectively), which is more favorable than the situation reported in the most reviewed studies concerning extremity osteosarcoma. (13,29,32) This nding could be explained by the shorter local drugretention time since the pelvis has a more su cient blood supply and drainage.…”
Section: Discussionmentioning
confidence: 99%
“…(25)(26)(27) As a modi ed approach to augment the potential of chemotherapy drugs, the AI technique combined with MSCs has been studied for years. (13,28,29) In the present study, we attempted to investigate the therapeutic effect of the CAI + MSC + S protocol in osteosarcoma treatment. The 5-year OS and EFS rates were 57.8% and 52.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations